Kontestasi Narasi Dan Relasi Interpersonal Dalam Organisasi Dakwah: Kajian Kritis Terhadap Hegemoni Simbolik Dalam Produksi Otoritas Keagamaan - Muhamad Haeril Ansori (STAI Bumi Silampari, 2026)
This study aims to critically analyze the contestation of religious narratives and the dynamics of interpersonal relations within dakwah organizations, as well as to uncover the mechanisms of symbolic hegemony in the production and legitimation of religious authority. This research employs a qualitative approach with an interpretative-critical orientation, utilizing a critical case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving five key informants from several dakwah organizations in Lombok. The data were analyzed using an interactive model, complemented by critical discourse analysis to examine the interplay between narrative construction, power relations, and symbolic practices. The findings reveal that religious narratives within dakwah organizations are not neutral but are socially constructed, negotiated, and legitimized through complex power relations. Symbolic hegemony operates through cultural legitimacy, institutionalized cadre systems, and interpersonal networks, which collectively shape the distribution of religious authority. At the same time, the study identifies emerging forms of resistance, particularly from younger actors and socially engaged groups, who promote more contextual, participatory, and inclusive approaches to dakwah. These dynamics illustrate that narrative contestation is an ongoing dialectical process between domination and transformation. The study implies that the development of dakwah practices requires a shift from hierarchical and exclusive models of authority toward more participatory and dialogical frameworks. It emphasizes the importance of redistributing symbolic power, fostering intersubjective dialogue, and recognizing diverse interpretations as part of achieving symbolic justice.